The 2010 Amendments and Hryniak v Mauldin: The Perspective of the Lawyers Who Have Lived Them - Kennedy, Gerard J. (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2020)
Through a survey of 90 lawyers with litigation experience, the author sought to determine the effects of recent amendments to Ontario procedural law [2010 Amendments] and a leading Supreme Court of Canada case [Hryniak] interpreting those amendments. The results were mixed. Most respondents viewed Hryniak and the 2010 Amendments as, overall, positive. But this was hardly a unanimous view. While Hryniak has certainly had effects, most respondents viewed the effectiveness of Hryniak and the 2010 Amendments to be limited, as other factors have intervened or remained as access to justice obstacles. While there was some perception that a culture shift has begun to emerge, the extent of that culture shift has been restricted. The responses did not lack all hope, but they ultimately suggest that the battle for access to civil justice must continue to be waged on multiple fronts.